Hugo Grotius and international relations - Bull, Hedley; Kingsbury, Benedict; Roberts, Adam, 1940- (Clarendon Press ; Oxford Univ. Press, 1990)
The author reappraises Grotius' thought and assesses the strengths and weaknesses of the 'Grotian' tradition - one which accepts the sovereignty of states but at the same time stresses the existence of shared values and the necessity of rules.